Determinants of Treatment Adherence Among Patients Living With Noncommunicable Diseases: A Mixed-Method Study in a Rural Area of West Bengal. (September 2021) - Banerjee, Ankush; Paul, Bobby; Dobe, Madhumita; Bandyopadhyay, Lina; Bhattacharyya, Madhumita; Sahu, Monalisha
The multisectoral impact of the COVID-19 pandemic can impair treatment adherence of patients with noncommunicable diseases (NCDs). This mixed-method study, conducted from November 2020 to January 2021, assessed the quantum of their treatment adherence and its determinants in rural West Bengal. Quantitative data were collected from 213 NCD patients while qualitative exploration for barriers of treatment adherence was conducted as 6 in-depth Interviews. Treatment adherence was assessed by "Medication Compliance Questionnaire" and "Adherence to Healthy Lifestyle and Follow-up Advice" Questionnaire. A total of 39.4% were nonadherent to medications while 67.1% had nonadherence to healthy lifestyle and follow-up advice. Significant predictors associated with nonadherence were increasing age, female gender, lower socioeconomic status, decreasing patient empowerment, and decreasing trust in the medical profession. Economic crisis, fear of contagion, and nonavailability of investigation facilities were some new emerging barriers in addition to preexisting barriers of treatment adherence. Therefore, measures for improving patient empowerment and patient–provider relationship by motivation and counseling, taking proper care of vulnerable patients affected by the pandemic, and correcting deficiencies at the health-system level should be given utmost priority.